Earth : 50 great science experiments and projects - Oxlade, Chris ([Lanham, Md.] : Distributed in the USA and Canada by National Book Network, 2003)
Contains fifty science experiments and projects designed to teach elementary school students about how the Earth works.
Includes index.
6.1
5-8
Keywords: Earth sciences -- Experiments -- Juvenile literature; Earth sciences -- Experiments; Experiments; Earth sciences -- Experiments; Science -- Experiments